2015
DOI: 10.1007/s10529-015-1785-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical force and tensile strain activated hepatic stellate cells and inhibited retinol metabolism

Abstract: Mechanical force and tensile strain significantly activate HSCs by regulating the retinoid metabolic pathway. Activation of HSCs can therefore be manipulated through mechanical force and tensile strain in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Activated HSCs were plated onto collagen-coated BioFlex amino-culture plates (Flexcell International, McKeesport, PA, USA) and grown in DMEM without FBS for 24 h. HSCs were then subjected to a 10% tensile strain, 0.5 Hz for 24 h by using Flexercell FX-2000 system (Flexcell International), as previously described (18). …”
Section: Methodsmentioning
confidence: 99%
“…Activated HSCs were plated onto collagen-coated BioFlex amino-culture plates (Flexcell International, McKeesport, PA, USA) and grown in DMEM without FBS for 24 h. HSCs were then subjected to a 10% tensile strain, 0.5 Hz for 24 h by using Flexercell FX-2000 system (Flexcell International), as previously described (18). …”
Section: Methodsmentioning
confidence: 99%
“…In this study, we observed the differential expression of multiple phenotype-determining genes upon the restoration of miR-16 expression at 48 h in myofibroblasts. HSC-specific adipogenic genes, including RXRα 32 – 34 , PPARγ 32 35 , CEBPα 32 , 36 , 37 , CEBPθ 2 , 32 , Fabp6 2 , 32 , Fabp7 2 , 32 , and Rbp2 38 , 39 , etc., were upregulated with the expression of miR-16. miR-16 also downregulated major fibrosis-inducing cytokines and related genes ( TGFβ2 40 , LTBP4 41 , etc.)…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that such factors regulate cellular proliferation and differentiation. Numerous studies have demonstrated that mechanical force, such as pressure and stretch, is an important regulator in cell metabolism (2830). The present study suggested that portal hypertension significantly inhibited the synthesis of hepatocellular glycogen.…”
Section: Discussionmentioning
confidence: 99%